ANALISIS PENGARUH INDEKS PERSEPSI KORUPSI TERHADAP KETIMPANGAN PENDAPATAN DI INDONESIA - Fatihurroyyan, Lalu Muhammad; Wildana, Muhammad Dandy Alif (Journal of Development Economic and Social Studies, 2024)
This study attempts to examine the effect of corruption on income inequality in Indonesia. The study uses the gini ratio as a proxy for income inequality, serving as the dependent variable. The corruption perception index is used as a proxy for corruption, while several control variables such as economic growth, taxes, and foreign direct investment act as independent variables. Using the multiple linear regression method with time-series data, the results of this study show that the corruption perception index has a positive and significant impact on income inequality. These results indicate a tendency for the "grease the wheel" effect of corruption on income inequality in Indonesia.